2009
DOI: 10.1111/j.1365-2141.2009.07835.x
|View full text |Cite
|
Sign up to set email alerts
|

Mantle cell lymphoma with central nervous system involvement: frequency and clinical features

Abstract: SummaryReported rates of central nervous system (CNS) involvement in mantle cell lymphoma (MCL) are highly variable but substantial (4-26%). Data is lacking regarding risk factors for CNS relapse, and for those patients in whom CNS prophylaxis could be beneficial. We present single institution retrospective analysis of data of baseline features, clinical course, rate of CNS disease and putative risk factors in 62 patients with MCL (18 female, 44 male). CNS disease (all cases were symptomatic) occurred in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…Blastoid histology stands out as most consistently identified risk factor in smaller studies [84][85][86][87]. Chihara et al analyzed a large cohort of Japanese patients with MCL and found Ki67≥ 30 % to be the only predictor of CNS progression by multivariate analysis (HR 6.0 [95 % CI 1.9-19.4]).…”
Section: Other Histologic Subtypes Mantle Cell Lymphomamentioning
confidence: 97%
“…Blastoid histology stands out as most consistently identified risk factor in smaller studies [84][85][86][87]. Chihara et al analyzed a large cohort of Japanese patients with MCL and found Ki67≥ 30 % to be the only predictor of CNS progression by multivariate analysis (HR 6.0 [95 % CI 1.9-19.4]).…”
Section: Other Histologic Subtypes Mantle Cell Lymphomamentioning
confidence: 97%
“…Additionally, CSF analysis and radiographic imaging may be suffi cient to diagnose CNS involvement when it is present. In our review of the literature, we found four cases of mass lesions in the brain thought to be caused by MCL; however, none of these studies involved a tissue diagnosis (1,7,9). Since brain parenchymal involvement by non-Hodgkin's lymphoma is rare, Doolittle et al suggested that the clinician should strongly consider doing a stereotactic brain biopsy with microscopic examination (9).…”
Section: Discussionmentioning
confidence: 95%
“…antle cell lymphoma (MCL) accounts for approximately 5% to 10% of non-Hodgkin's lymphoma cases (1)(2)(3)(4). Typically MCL presents in the fi fth to sixth decades of life with generalized lymphadenopathy and extranodal involvement (bone marrow, gastrointestinal tract, blood) (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The propensity for CNS involvement by Burkitt's lymphoma has also been well described, with an 8-10% incidence at diagnosis, and up to 30-50% throughout the course of disease [12]. Mantle cell lymphoma (MCL) has been reported to be associated with an unexpected high risk of CNS involvement, estimated at 4-6% [13]; Feugier et al 2004; [14,15]. However, such risks may be attributed to poor systemic control of disease, and CNS relapse in MCL is rare with modern therapies.…”
Section: Incidence and Risk Factorsmentioning
confidence: 97%